Exploring perceptions of intracity vehicle owners on adopting compressed natural gas (CNG) as an alternative fuel in Dar es Salaam City, Tanzania - Msomi, Josephat D.; Onesmo, Clashon L. (AGUSPATI Research Institute, 2025)
The rapid expansion of urban areas in developing countries has significantly increased transportation demand, leading to air pollution and posing serious health and environmental risks. This situation calls for alternative fuels, especially in the transport sector. Thus, this study aimed to understand how vehicle owners within the city perceive the adoption of CNG as an alternative fuel in Dar es Salaam, Tanzania. A sample of 384 participants was selected using stratified and purposive sampling methods. Data collection involved questionnaires via Google Forms and interviews. The data were analyzed descriptively and inferentially using IBM SPSS version twenty seven (27) and Microsoft Excel, with both descriptive and inferential methods. Results indicate that while general awareness of CNG is moderate, those with direct experience have a much better understanding of its environmental and cost-saving advantages. Adoption is limited by technical knowledge gaps and infrastructure issues. Still, attitudes toward adopting CNG are mostly positive, driven by economic and environmental concerns. The study highlights the need for public campaigns and supportive legal and institutional frameworks to increase awareness and convert positive attitudes into actual use, offering valuable guidance for policy efforts to promote sustainable urban Transportation.